A case of unilateral trade liberalization: The autonomous abolition of industrial tariffs by Switzerland in 2024 - Thomas A. Zimmermann (Aussenwirtschaft, 2023)
On 1 January 2024, Switzerland will implement a major trade policy reform by autonomously eliminating all tariffs on imports of industrial products regardless of their origin. After a brief review of the literature on unilateral trade liberalization and the current Swiss tariff landscape, this paper presents the motivation and the substance of the reform. The elimination of industrial tariffs will reduce the net fiscal burden on imports by around CHF 600 million per year. In addition, imports will be easier to administer, as the Swiss customs tariff will be simplified (thanks to a reduction in tariff numbers) and proofs of origin will no longer be required for goods that remain in Switzerland. We summarize the main findings of studies carried out in the run-up to the reform. The political process and debates leading up to parliamentary approval of the reform, its reception in international fora and the ongoing work on implementation are presented as well. I conclude that the difficult process of obtaining parliamentary approval confirms the insights from the political economy literature that unilateral trade liberalization is politically difficult to achieve in a purely domestic context, despite the economic benefits it brings. From an economic perspective, the contribution of unilateral liberalization to domestic market opening is substantial and has certain advantages, also in comparison to other trade policy instruments such as free trade agreements (FTAs). Unilateral liberalization and preferential liberalization through FTAs need not be mutually exclusive but can be seen as complementary trade policy tools.
Keywords: F13; 330; free trade; tariffs; unilateral liberalization; autonomous trade policy